The Roles of Women on Decision-Making And Implementation of Corn Planting in Wera District Bima Regency - Hayati Hayati (Jurnal Penelitian Pendidikan IPA, 2023)
Women have a role in activities in the agricultural sector including in corn cultivation. Success in corn production cannot be separated from the contribution of women who also work in corn cultivation activities. Therefore, this study aims to analyze the role of women in decision making and in the implementation of corn cultivation, its impact and the factors that influence this which is carried out in Wera Regency, Bima Regency. Retrieval of data using survey methods through interviews with questionnaires on 68 respondents. Data analysis used descriptive statistical methods and multiple linear regression tests. The results showed that the role of women in making decisions and implementing corn cultivation was included in the high category. The impact of the role of women in decision making and implementation of cultivation can be observed significantly in the managerial and optimization of corn cultivation results. Internal and external factors have no significant effect on women's role in decision making